Impact of real sector variables on Shari'a compliant stock returns - Muhammad Hanif; Zulfiqar A. Shah; Abdullah M. Iqbal (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2015)
Shari'a compliant stocks are a recent development under Islamic finance, whereby stocks are screened through Shari'a compliance filters. This study is conducted to understand and document the important Real Sector macroeconomic factors contributing in determining stock prices of Shari'a compliant companies in Pakistan. Our sample includes all 97 non-financial companies screened by Al-Meezan Investment Management Ltd, based on financial results of 2009. We have included Six Macroeconomic variables in addition to market index in our study for ten years period (2001-10). Results identified Zero real sector variable in pricing, however, with the inclusion of market index in analysis, the single important variable in pricing of Shari'a compliant securities is market Beta. Evidence favors CAPM for pricing of securities in local market as market index captures the risk of macroeconomic variables.
Keywords: 330; shari'a compliant securities; macroeconomic variables; APT; KSE; Pakistan